(x2+y2)2=xy

Asked by Pranshu Chadha | 17th Nov, 2012, 01:40: PM

Expert Answer:

Answer: Given : (x2+y2)2 = xy
differentiating wrt x , we get
=>2 (x2+y2) *d/dx(x2+y2 ) = d/dx(xy)   {using d/dx {x2} = 2x}
=> 2 (x2+y2) (2x + 2 y (dy/dx) ) = x (dy/dx) + y {using product rule}
=> 4x (x2+y2) + 4 y (x2+y2) (dy/dx) = x (dy/dx) + y
=> 4x (x2+y2) -y = (x - 4 y (x2+y2) ) dy/dx 
=> dy/dx = (4x (x2+y2) -y ) / (x - 4 y (x2+y2) )  Answer

Answered by  | 17th Nov, 2012, 04:06: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.